Rancangan Sistem Pemantauan Lingkungan Berbasis IoT untuk Pertanian Padi - Yeni Natalia; Tata Sutabri (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
This study seeks to create a system for monitoring the environment using the Internet of Things. It aims to help farmers manage their rice fields in a way that is both effective and sustainable. The system will provide farmers with real-time data on soil moisture, air temperature, and rainfall, allowing them to make informed decisions. Sensors will collect this information, which will be analyzed and presented simply through a web or mobile app. Early simulations suggest that this system could boost crop yields by as much as 15% and cut water use and costs by 20%. These findings point to the IoT monitoring system as a practical means to enhance rice farming's efficiency and productivity. Yet, there are hurdles. Issues like poor network infrastructure, high costs of implementation, and the farmers' ability to adapt to this technology need to be overcome for the system to work properly. This study aspires to make a real difference in promoting sustainable farming practices while paving the way for more advanced IoT solutions in the future.